Effect of education on the incidence rate of occupational exposure resulting from sharp bodies and mucocutaneous contamination with blood and body fluids of patients among nursing personnel of Valiasr Hospital- Fassa, 2008 - Ghodsbin, Fariba; Bijani, Mostafa; Rahmati, Hashem; Mohebbi, Zinat; Kamali, M (Investigación y Educación en Enfermería, 2011)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To determine the effect of education on the incidence rate of occupational exposure resulted from sharp bodies and mucocutaneous contamination with blood and body fluids of patients among nursing personnel of Valiasr Hospital- Fassa, 2008. Methodology. Interventional study. Samples consisted of 120 nurses (60 as study group and 60 as control group) selected by systemic randomized allocation. The study group was trained in occupational exposure for a period of ten hours. The data collecting tool was an occupational exposure questionnaire that was completed for both groups, before and two months after education. A knowledge test was also applied to both groups before and after education. Data analysis was done by descriptive statistics, frequency, mean and standard deviation, inferential statistics, x², T-test and paired t, and a level of significance p<0.05 was statistically accepted. Results. Results of the research, indicated an increase of the knowledge level and a reduction of the incidence rate of occupational exposure among the study group in such a way that, the knowledge mean score of this group went from 8.1 before education to 14.1 after education (p<0.05). The incidence rate of occupational exposure resulting from sharp bodies and mucocutaneous contamination with blood and body fluids of patients was also reduced after education in the case group (p<0.05). Conclusion. The results of the study indicated improvement of knowledge and practice level in the the case group, concerning occupational exposure due to sharp bodies and mucocutaneous contamination with blood and body fluids of patients after the training intervention. In addition, continuous education in this respect is necessary because its effect lowers with time-lapse.